SAT0133 TREATMENT PATTERNS, PERSISTENCE, AND DURABILITY IN RHEUMATOID ARTHRITIS PATIENTS WITH INADEQUATE RESPONSE TO BIOLOGIC DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS (BDMARDS). (June 2019) - Dore, Robin K.; Antonova, Jenya; Burudpakdee, Chakkarin; Wang, Xin; Ozbay, Burak; Genovese, Mark C.
Abstract : Background: EULAR and ACR recommend bDMARDs, as monotherapy or in combination with methotrexate, in patients whose rheumatoid arthritis (RA) remains active despite methotrexate use. 1 Treatment options for bDMARD inadequate response (IR) patients vary. Understanding the real-world treatment patterns and treatment duration in bDMARD IR patients may help identify the most suitable next treatment. Objectives: We studied treatment patterns, treatment persistence, and treatment durability in bDMARD IR patients who switched to another treatment regimen. Methods: In US health plan claims data, this study selected adult RA bDMARD patients: those with ≥2 RA diagnoses ≥30 days apart, who newly initiated a bDMARD (1/1/2012 - 3/31/2017; baseline) and then switched to another bDMARD or JAKi (index date, ID). All patients had continuous ≥1-year enrollment before and after ID. Patient characteristics were evaluated at baseline; treatment patterns, persistence, and durability (duration) were evaluated during pre- and post-index periods. Kaplan-Meier curves were used to evaluate treatment persistence. Results: Among 105, 039 patients who were initiated on bDMARDs, 19, 085 (18%) demonstrated IR; among those, 4, 656 met all the selection criteria: median age 54 years, 22% male, 17% from Northeast, 26% Midwest, 42% South, 15% West. At baseline, 26% used tumor necrosis factor inhibitors (TNFi) monotherapy and 64% used TNFi in combination with conventional synthetic DMARD (csDMARD). Baseline median treatment duration was 8.3 months overall, including 5.8 months for monotherapy and 9.4 months for combination therapy. Upon switch, 46% of patients used monotherapy (28% TNFi, 11% other bDMARD, 7% janus kinase inhibitors [JAKi]), and 54% used bDMARD in combination with csDMARD (37% TNFi + csDMARD, 12% other bDMARD + csDMARD, 4% JAKi + csDMARD). Median treatment duration was longer for combination therapy than monotherapy (13.1 vs. 5.8 months, p<0.001). TNFi showed a trend towards shortest treatment duration and lowest 12-month treatment persistence among monotherapies and combination therapies. (Table) JAKi showed best treatment persistence among monotherapies (Figure 1 ; p-value=0.0004) and combination therapies (Figures 2 ; p-value<0.0001). Conclusion: In biologic DMARD IR patients, the first bDMARD treatment lasted, on average, for 8.3 months before switch. Post-switch, TNFi showed a trend towards the shortest durability and JAKi showed the longest durability. The data suggest substantial unmet need in bDMARD patients. A well-tolerated effective therapy, with potent clinical efficacy and improved treatment durability may benefit this patient population. Reference: [1] Singh J.A., et al. Arthritis & Rheumatology. 2016; 68(1):1-26. Disclosure of Interests: Robin K Dore Grant/research support from: Gilead Sciences, AbbVie, Amgen, Lilly, Pfizer, Regeneron, Sanofi, Consultant for: AbbVie, Amgen, Lilly, Speakers bureau: AbbVie, Amgen, Lilly, Sanofi, Regeneron, Pfizer, UCB, Jenya Antonova Shareholder of: Gilead Sciences, Employee of: Eli Lilly and Company, Medimmune, Genentech, Gilead Sciences, Chakkarin Burudpakdee Grant/research support from: Gilead Sciences, Xin Wang Grant/research support from: Gilead Sciences, Consultant for: Gilead Sciences, Burak Ozbay Shareholder of: Gilead Sciences, Employee of: Abbott Laboratories, Abbvie, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm